Review on Classification, Extraction and Application of Natural Dyes - Parth Patel,; Mineh D. Patel,; Dr. Satishkumar M Khadia,; Falguni. G Bhabhor, (International Journal of Scientific Research in Science and Technology, 2024)
India has over 450 plants capable of producing dyes. Dyes from natural sources such as plant leaves, roots, bark, insectsecretions and minerals. Natural dyes are mainly used for dyeing natural fibers such as cotton, wool and silk. Most natural colors have special properties such as antibacterial, low toxicity, allergenicity and UV protection. They have been used since ancient times and are widely accepted in various fields such as food, textiles, fine arts and papermaking. There are currently many different dye extraction methods/processes, including Solvent extraction, aqueous extraction, enzymatic extraction, etc. All these extraction methods have their advantages and disadvantages. Experimental results show that it performs well with all natural dyes and may be a better alternative to synthetic dyes. In recent years, it has been observed that synthetic dyes have many drawbacks, such as toxicity, pollution, and allergenicity, but natural dyes do not have such drawbacks. This article discusses the types of natural dye sources and their extraction methods, classification, environmental benefits, and other uses.
Keywords: Natural Dyes; Classification; Extraction-Method; Application; Eco-Friendly; Recent Advancement